Exploiting the Anti-Biofilm Effect of the Engineered Phage Endolysin PM-477 to Disrupt In Vitro Single- and Dual-Species Biofilms of Vaginal Pathogens Associated with Bacterial Vaginosis - Joana Castro; Lúcia G. V. Sousa; Ângela França; Lenka Podpera Tisakova; Lorenzo Corsini; Nuno Cerca (MDPI AG, 2022)
Bacterial vaginosis (BV) is the most frequent vaginal infection in women of reproductive age. It is caused by the overgrowth of anaerobic vaginal pathogens, such as Gardnerella vaginalis, Fannyhessea vaginae, and Prevotella bivia, which are vaginal pathogens detected during the early stages of incident BV and have been found to form multi-species biofilms. Treatment of biofilm-associated infections, such as BV, is challenging. In this study, we tested the role of an investigational engineered phage endolysin, PM-477, in the eradication of dual-species biofilms composed of G. vaginalis-F. vaginae or G. vaginalis-P. bivia. Single-species biofilms formed by these species were also analysed as controls. The effect of PM-477 on biomass and culturability of single- and dual-species biofilms was assessed in vitro using a microtiter plate assay, epifluorescence microscopy, confocal laser scanning microscopy, and quantitative PCR. The results showed that PM-477 was particularly effective in the disruption and reduction of culturability of G. vaginalis biofilms. In dual-species biofilms, PM-477 exhibited lower efficiency but was still able to selectively and significantly eliminate G. vaginalis. Since polymicrobial interactions have been shown to strongly affect the activity of various antibiotics, the activity of PM-477 in dual-species biofilms is a potentially promising result that should be further explored, aiming to completely eradicate multi-species biofilms associated with BV.